Effects of different training amplitudes on heart rate and heart rate variability in young rowers - Vaz, M. S.; Picanço, L. M.; Del Vecchio, F. B. (The Journal of Strength and Conditioning Research, 2014)
The aim of this study was to investigate the autonomic nervous system recovery and the psychological response as a result of 3 training amplitudes on heart rate (HR), heart rate variability (HRV), and rate of perceived exertion (RPE) in rowing. Eight young rowers (16.8 ± 1.4 years) performed, in a randomized fashion, 2 sessions of high-intensity interval training, with high and low amplitude and a continuous training (CT) session, with the same exercise duration (10 minutes) and mean intensity (60% of maximal stroke test). The data of HR, HRV, and RPE were collected 5 minutes before, immediately after each session, and 24 hours later. High amplitude promoted higher impact in maximum HR (p < 0.05) and RPE (p < 0.001) when compared with CT. For the time domain HRV variable, there was a statistically significant difference between moments of rest (pretraining or post 24 hours) and posttraining in all training sessions. Originally, we conclude that training with higher load variation between effort and recovery impacts HRV, HR, and RPE with greater intensity, but the younger rowers were ready for new training sessions 24 hours after either training method. Coaches can use the polarized training method, observing the stimulus nature and time required for recovery, because it may be an adequate strategy for the development of rower's conditioning.